2021
DOI: 10.1088/1361-6463/abf36f
|View full text |Cite
|
Sign up to set email alerts
|

NO PLIF flow visualization and time-resolved temperature distributions in laser induced breakdown plumes

Abstract: NO planar laser induced fluorescence (PLIF) is used to obtain images of laser-induced breakdown plasma plumes in NO-seeded nitrogen and dry air at near atmospheric pressure. Single-shot PLIF-images show that the plume development 5–50 μs after the breakdown pulse is fairly reproducible shot-to-shot, although the plume becomes increasingly stochastic on longer timescales, 100–500 μs. The stochastic behavior of the plume is quantified using probability distributions of the loci of the plume boundary. Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Experimental and numerical results of the plasma kernel formation predicted a two-lobed structure in air [65][66][67] and high pressure argon plasma irradiated through an excimer laser [68]. An experimental and modeling study of laser induced breakdown also confirmed the generation of the third lobe [69][70][71][72][73], whereas, the appearance of a four-lobed structure for successive laser pulse was reported due to a beam focus at a larger offset (∼2.5 mm) [74]. The formation of a fourth lobe was also reported due to upstream focusing at a stoichiometric mixture [75] and a larger pulse interval [76,77].…”
Section: Introductionmentioning
confidence: 79%
“…Experimental and numerical results of the plasma kernel formation predicted a two-lobed structure in air [65][66][67] and high pressure argon plasma irradiated through an excimer laser [68]. An experimental and modeling study of laser induced breakdown also confirmed the generation of the third lobe [69][70][71][72][73], whereas, the appearance of a four-lobed structure for successive laser pulse was reported due to a beam focus at a larger offset (∼2.5 mm) [74]. The formation of a fourth lobe was also reported due to upstream focusing at a stoichiometric mixture [75] and a larger pulse interval [76,77].…”
Section: Introductionmentioning
confidence: 79%